Expression of Npas4 mRNA in Telencephalic Areas of Adult and Postnatal Mouse Brain - Damborsky, Joanne C.; Slaton, G. Simona; Winzer-Serhan, Ursula H. (Frontiers in Neuroanatomy, 2015)
The transcription factor neuronal PAS domain-containing protein 4 (Npas4) is an inducible immediate early gene which regulates the formation of inhibitory synapses, and could have a significant regulatory role during cortical circuit formation. However, little is known about basal Npas4 mRNA expression during postnatal development. Here, postnatal and adult mouse brain sections were processed for isotopic in situ hybridization using an Npas4 specific cRNA antisense probe. In adults, Npas4 mRNA was found in the telencephalon with very restricted or no expression in diencephalon or mesencephalon. In most telencephalic areas, including the anterior olfactory nucleus (AON), piriform cortex, neocortex, hippocampus, dorsal caudate putamen (CPu), septum and basolateral amygdala nucleus (BLA), basal Npas4 expression was detected in scattered cells which exhibited strong hybridization signal. In embryonic and neonatal brain sections, Npas4 mRNA expression signals were very low. Starting at postnatal day 5 (P5), transcripts for Npas4 were detected in the AON, CPu and piriform cortex. At P8, additional Npas4 hybridization was found in CA1 and CA3 pyramidal layer, and in primary motor cortex. By P13, robust mRNA expression was located in layers IV and VI of all sensory cortices, frontal cortex and cingulate cortex. After onset of expression, postnatal spatial mRNA distribution was similar to that in adults, with the exception of the CPu, where Npas4 transcripts became gradually restricted to the most dorsal part. In conclusion, the spatial distribution of Npas4 mRNA is mostly restricted to telencephalic areas, and the temporal expression increases with developmental age during postnatal development, which seem to correlate with the onset of activity-driven excitatory transmission.